Java 7 for absolute beginners - Bryant, Jay (Apress, 2012)
Java 7 Programming for Absolute Beginners introduces the new core, open source Java Development Kit. Its focus is on practical knowledge and its completeness—it provides all the bits and pieces an utter novice needs to get started programming in Java. It seems as if everyone is writing applications or apps these days for Android, BlackBerry, and the enterprise—it's where the money's at. But, how do they do it? Well, it's best to start by learning Java, one of the most popular programming languages around these days, still. Yes, that's right. This book: (1) teaches Java development in language anyone can understand, giving you the best possible start, (2) provides simple, step-by-step examples that make learning easy, allowing you to pick up the concepts without fuss, and (3) offers clear code descriptions and layout so that you can get your code running as soon as possible.